2017
DOI: 10.4018/ijcbpl.2017040101
|View full text |Cite
|
Sign up to set email alerts
|

Technology Acceptance Theories

Abstract: Studying the acceptance and usage of technologies has become one of the most significant fields in software engineering domain. In order to explain the individuals' usage behavior towards technologies, many theories and models have been proposed over the years. This research paper focuses on reviewing a group of ten technology acceptance theories and models by studying their structure, evolution stages, and their strengths and weaknesses points. These theories were analyzed and classified into two main types d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(53 citation statements)
references
References 38 publications
0
50
0
3
Order By: Relevance
“…Digital transformation leads to a work transformation, which involves a reorganisation of work and ultimately changes the way people work (Anderson-Connolly et al , 2002). In this context, the acceptance of new technology as part of the daily routine is essential (Momani and Jamous, 2017). Technology acceptance is considered one of the main success factors of new technologies (e.g.…”
Section: Theory: the Covid-19 Pandemic And The Digital Transformation Of Workmentioning
confidence: 99%
“…Digital transformation leads to a work transformation, which involves a reorganisation of work and ultimately changes the way people work (Anderson-Connolly et al , 2002). In this context, the acceptance of new technology as part of the daily routine is essential (Momani and Jamous, 2017). Technology acceptance is considered one of the main success factors of new technologies (e.g.…”
Section: Theory: the Covid-19 Pandemic And The Digital Transformation Of Workmentioning
confidence: 99%
“…Numerous studies have given significant importance to technology acceptance theories. For instance, the innovation diffusion theory (Rogers, 1962) stated that attributes like compatibility, relative advantage (perceived usefulness), observability, trialability, and complexity (ease of use) were the parameters that would help to determine an individual's adoption of innovation (Momani and Jamous, 2017). The theory of reasoned action developed as a theory of planned behavior (Ajzen, 1991), has been widely used in several applications in diverse fields, i.e., technology, by the addition of perceived behavioral control.…”
Section: Technology Acceptance: Theories and Modelsmentioning
confidence: 99%
“…Furthermore, a Unified Theory of Acceptance and Use of Technology (UTAUT) proposed by Venkatesh et al (2003) indicated that effort expectancy, performance expectancy, and social influence proved to be the factors that determine the intention and behavior of technology use. Studies focusing on Information and Communication Technology (ICT) have been incorporating recent developments of deterring factors in their theories to fulfill needs and improve facilities, as these are essential prerequisites for the technology's utilization, realization, and acceptance (Momani and Jamous, 2017). Although ICT creates innovation and incorporates the theories into action, a lack of knowledge and proper awareness would hinder them from availing the benefits of these services provided by the government and private sectors (Reffat, 2003).…”
Section: Technology Acceptance: Theories and Modelsmentioning
confidence: 99%
“…The Theory of Planned Behaviour is also derived from the Decomposed Theory of Planned Behaviour (DTPB). The Theory behind Technology Acceptance Model (TAM) has been derived from The Theory of Reasoned Action TRA [9]. The Technology Acceptance Model (TAM) has been applied to various disciplines of research.…”
Section: Conceptual Framework and Literature Reviewmentioning
confidence: 99%